Study of Correlation: Science Process Skills and Persistence Character of Middle School Students - Harizon; Asrial; Haryanto; Kurniawan, Dwi Agus; Rini, Endah Febri Setiya; Aldila, Febri Tia; Fitriani, Riska; Sinaga, Feliza Paramitha (Universitas Pendidikan Ganesha, 2024)
Science process skills are one of the important aspects of science learning. This research aims to analyze the relationship between science process skills and the character of students' persistence when following the learning process. This study uses Mix Methods research by combining quantitative and qualitative research. Data collection techniques in this study use the instrument of the scientific process skills observation sheet, the character questionnaire and interview sheet. The sampling technique in this study uses cluster random sampling. The sample in this study totalled 224 Student and Interviewer with 3 Natural Sciences teachers and students in each school. Data analysis techniques in this study use descriptive statistics and Pearson correlation tests for quantitative data and use the Miles and Huberman methods for qualitative data analysis. The results of this research are that the relationship between science process skills and students' persistence character at school is 0.784%. The conclusion of this research is that the average student's science process skills and persistence character are categorized as good and there is a relationship between science process skills and perseverance character. Recommendations for further research are to develop learning innovations that can be useful to improve the skills of science and perseverance of students in learning science.